Draft Genome Sequence of the Strict Anaerobe Clostridium neopropionicum X4 (DSM 3847(T)) - Beck, Matthias H. (Genome Announc, 2016)
Here, we report the draft genome sequence of Clostridium neopropionicum X4 (DSM 3847(T)), a strictly anaerobic bacterium capable of fermenting ethanol and CO(2) to propionate, acetate, and propanol. The genome consists of a single chromosome (3.19 Mb).